Kajian Kesesuaian Wisata Dan Daya Dukung Kawasan Wisata Sungai Bingai Namu Sira-Sira Langkat Sumatera Utara Study on Suitability and Carrying Capacity of Bingai River Namu Sira-Sira at Langkat Regency Nothern Sumatera. - Riris Romaito; Pindi Patana; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Bingai River Namu Sira-Sira is one of destination for water recreation such as rafting and bathing specially for local tourists. Since the number of visitors increased, Bingai River quality of water changed such as the physics, chemistry and biology characteristics. The purpose of this research is to examine the characteristics of the Bingai River Namu Sira-Sira based on the suitability and carrying capacity at destination well as assess the perceptions of visitors to tourist activity at Bingai River Namu Sira-Sira at Langkat Regency Nothern Sumatra. The analysis used in this study is a descriptive analysis, the suitability index and carrying capacity of the area for rafting and bathing category. It resulted suitability index, for rafting and bathing was on criteria stratum 1 (very suitable). The carrying capacity of the research areas baths are 3.405 and rafting is 19.875 people. Based on interview, visitors was comfortable and satisfied with the attraction.Keywords : River Ecosytem, Ecotourism, Carrying Capacity.